Substation of claim from 26 february 2018 to 25 March 2018 due to defective fiaphragm – 04.04.18 - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding the substation of claim from 26 February 2018 to 25 March 2018 due to defective diaphragm of BRACU new campus development project.